A giant pancreatic pseudocyst treated by cystogastrostomy. (24th March 2015) - Wang, Grace C; Misra, Subhasis
Abstract : We report a case of a giant pancreatic pseudocyst in a 65-year-old man presenting with abdominal pain, loss of appetite and abdominal distension. CT scans demonstrated a giant pancreatic pseudocyst measuring 25.7 cm×15.3 cm×10.9 cm anteroposteriorly, with significant compression of surrounding organs. An open cystogastrostomy was performed through a midline incision, and 3 L of fluid was drained from the giant pseudocyst. Recovery has been uneventful.